Factors influencing adherence in CML and ways to improvement: Results of a patient-driven survey of 2546 patients in 63 countries - Geissler, Jan; Sharf, Giora; Bombaci, Felice; Daban, Mina; De Jong, Jan; Gavin, Tony; Pelouchova, Jana; Dziwinski, Euzebiusz; Hasford, Joerg; Hoffmann, Verena Sophia (Journal of cancer research and clinical oncology, 2017)
Optimal adherence to CML therapy is of key importance to maximize treatment effectiveness. Two clinical studies (ADAGIO and Hammersmith) have proven a clear correlation between adherence and achieving optimal treatment response and have revealed that non-adherence is common in CML patients (Marin et al. in J Clin Oncol 28(24):2381-2388, 2010, Noens et al. in Haematologica 99(33):437-447, 2014). The aim of this study is to assess the extent of suboptimal adherence and to investigate motivations and behavioural patterns of adherence in a worldwide patient sample. Questionnaires were provided by the CML Advocates Network and were filled in by patients online and offline. Patient characteristics, treatment and motivations were collected. Adherence was assessed by the 8-item Morisky Medication Adherence scale. Logistic regression models were fitted to investigate the influence of different factors on adherence. Overall, 2 546 questionnaires from 63 countries and 79 CML patient organisations were evaluable. 32.7% of participants were highly adherent, 46.5% were in the medium and 20.7% in the low adherence group. Factors increasing the probability of being in the high adherence group are older age, male sex, management of side effects, only one tablet per day and feeling well informed about CML by the doctor. More than 2 years since diagnosis were significantly lowering the chance as was the use of reminding tools. Living arrangements, multiple medication and personal payment obligations increased the probability to be at least in the medium adherent group. This is the most comprehensive study conducted to date to gain knowledge about factors causing non-adherence in CML. Better information on the disease, medication and management of side effects, supported by haematologists, is key to improve adherence.
Keywords: Male; chronická myeloidní leukemie; Adherence patient motivations; lidé středního věku; Optimal adherence; senioři nad 80 let; Tyrosine kinase inhibitors; protinádorové látky; Aged, 80 and over; Haematology; Sex Factors; Age Factors; Surveys and Questionnaires; Driving factors of nonadherence; Humans; Chronic myeloid leukaemia; Middle Aged; senioři; hodnocení adherence k farmakoterapii; Antineoplastic Agents; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; Female; mladiství; Aged; Behavioural patterns of adherence; Morisky Medication Adherence scale; ženské pohlaví; Factors causing nonadherence; průzkumy a dotazníky; věkové faktory; Patient advocacy; Assessment of Medication Adherence; mladý dospělý; Adult; Young Adult; sexuální faktory; Patient-driven survey; CML treatment adherence; Adolescent; dospělí; lidé; Molecular response